Digital Cues with Immersive Vignettes: Pioneering AI-Generated Video Reels to Study Barriers to Knowledge Flow - Keeler, Justin B.; Brock Baskin, Meagan E.; McKee, Victoria (Journal of Knowledge Management Practice, 2025)
This study investigates how psychological constructs impact a social dynamic of exclusion by pioneering the experimental usage of AI-generated video reels. Exclusion can be a critical barrier in knowledge flow within organizations, thus impairing information sharing and learning. In our 2x2 study, analysis found 172 graduate students were at increased propensity to feel ostracized based on a mindset and an elicited social schema/axiom (belief system). Results provide a preliminary explanation link (via exclusion) between bottom-line mentality (BLM) and knowledge hiding/concealment practices that can disrupt information flows at individual and group levels. Our experimental technique is the first of its kind.
Keywords: knowledge management; artificial intelligence; bottom-line mentality; zero-sum belief; ostracism; experimental